RENAL BIOCHEMISTRY PROFILE OF KIDNEY IN THE TUMBES CROCODILE (CROCODYLUS ACUTUS) REARED IN CAPTIVITY IN THE NORTH OF PERU - Horikawa K., Verónica (2013)
The aim of the study was to determine the biochemistry profile of the kidney in the Tumbes crocodile (Crocodylus acutus) reared in captivity in the north of Peru (Tumbes). Blood samples (6 ml) by puncture of the post-occipital venous sinus were collected to 60 males (24 juveniles, 27 sub-adults, and 9 adults). All animals were manually restrained. Values for uric acid was 74.2 ± 25.0 mg/L, creatinine 1.49 ± 0.39 mg/L, calcium 10.8 ± 2.4 mg/dl, and phosphorus 5.3 ± 2.0 mg/dl. There was significant difference (p<0.05) between juveniles and sub-adults for uric acid and creatinine, and adults versus younger animals for calcium, whereas phosphorus values were not affected by age.